HYDRODYNAMIC CAVITATION IN VENTURI CHANNELS WITH DIFFERENT DIVER-GENT ANGLES - Biluš, Ignacijo; Lešnik, Luka; Kevorkijan, Luka (Journal on Processing and Energy in Agriculture, 2026)
Hydrodynamic cavitation occurs in hydraulic systems when flow restrictions increase velocity and decrease pressure below vapor pressure. To study cavitation phenomena, simplified geometries such as Venturi channels are commonly used for experiments and numerical modeling. A Venturi channel gradually narrows to a throat before expanding at a divergent angle, influencing cavitation characteristics. This study experimentally investigates the effect of divergent angles on cavitation formation and dynamics. Three 3D-printed inserts with different divergent angles were tested in a plexiglass cavitation tunnel. High-speed imaging (20,000 fps) with a Photron Fastcam SA-Z captured cavitation behavior, and an in-house Python script analyzed vapor projected area (a proxy for vapor volume) and cavity length. Results show that increasing the divergent angle reduces attached cavity length but produces larger detached cavitation clouds that travel farther before collapsing. The total cavitation projected area increased with larger divergent angles due to upstream movement of the cloud shedding point. These findings highlight the significant influence of divergent angle on cavitation behavior, with potential implications for cavitation-induced effects like erosion.
Keywords: cavitation, Venturi, high-speed video, cloud shedding, image postprocessing